2020
DOI: 10.1007/s10072-020-04244-5
|View full text |Cite
|
Sign up to set email alerts
|

Why we fail: mechanisms and co-factors of unsuccessful thrombectomy in acute ischemic stroke

Abstract: Purpose Mechanical thrombectomy (MT) is an effective treatment for patients suffering from acute ischemic stroke. However, recanalization fails in about 16.5% of interventions. We report our experience with unsuccessful MT and analyze technical reasons plus patient-related parameters for failure. Methods Five hundred ninety-six patients with acute ischemic stroke in the anterior circulation and intention to perform MT with an aspiration catheter and/or stent retriever were analyzed. Failure was defined as 0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
1
17
1
3
Order By: Relevance
“…Regarding EVT outcomes, successful recanalization was achieved in 88% of EVT patients, a rate that is within the upper range of rates reported from large EVT trials and registries (15,(25)(26)(27). Among transferred patients, patients who underwent EVT had a trend for better functional outcome at 3 months after the index event compared to patients excluded from EVT.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding EVT outcomes, successful recanalization was achieved in 88% of EVT patients, a rate that is within the upper range of rates reported from large EVT trials and registries (15,(25)(26)(27). Among transferred patients, patients who underwent EVT had a trend for better functional outcome at 3 months after the index event compared to patients excluded from EVT.…”
Section: Discussionsupporting
confidence: 54%
“…As unsuccessful recanalization predictably leads to poor patient prognosis, it is important to identify the factors associated with unsuccessful recanalization. Factors associated with such unsuccessful recanalization include greater age, stroke severity, occlusion due to atherosclerosis, and thrombus burden [ 7 , 8 , 9 ]. Nonetheless, further research is still needed to identify the factors involved in unsuccessful recanalization [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with such unsuccessful recanalization include greater age, stroke severity, occlusion due to atherosclerosis, and thrombus burden [ 7 , 8 , 9 ]. Nonetheless, further research is still needed to identify the factors involved in unsuccessful recanalization [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the impact of baseline serum glucose levels (BGL) on recanalization success, especially in BAO stroke patients, remains uncertain. While acknowledging a history of diabetes mellitus as potential factor, most previous studies investigating reasons for unsuccessful recanalization did not specifically analyze BGL [10,13]. A recent study observed that diabetes mellitus was associated with an increased likelihood of a first pass effect [14].…”
Section: Introductionmentioning
confidence: 99%